Carriage of multidrug-resistant bacteria among pediatric patients before and during their hospitalization in a tertiary pediatric unit in Tunisia. Issue 1 (1st January 2018) - Tfifha, Miniar; Ferjani, Asma; Mallouli, Manel; Mlika, Nesrine; Abroug, Saoussen; Boukadida, Jalel
ABSTRACT: The pandemic spread of multidrug-resistant (MDR) bacteria (i.e., methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum b-lactamase-producing Enterobacteriaceae (ESBLPE), vancomycin-resistant enterococci, carbapenemase-producing Enterobacteriaceae (CPE), multiresistant Pseudomonas aeruginosa and multiresistant Acinetobacter baumannii ) pose a threat to healthcare Worldwide. We found limited data of MDR bacteria in pediatric patients hospitalized in Tunisian tertiary healthcare.The aim of the study is to evaluate the acquisition rate of MDR acquisition during hospitalization and to explore some of the associated risk factors for both carriage and acquisition at the pediatric department, Sahloul University Hospital. During September and October 2016, newly admitted patients were screened, at admission, during care and at discharge. Risk factors for colonization were explored by multivariate analysis. Of 112 newly admitted patients, 8.92% were colonized with at least one MDR. No risk factor was identified at admission. During hospitalization, five newly acquisition MDR (4.9%) were detected and eight (7.84%) at discharge. The specie most frequently detected on admission was Escherichia coli (50%), whereas, on discharge, Escherichia coli and K. pneumoniae were the species most frequently detected (52.7%). The pediatric intensive care unit (PICU) hospitalization, the length of hospital stay (more than 3days) and age under 2 years were identified as risk factor for acquisition of MDR during hospitalization. We identified several independent risk factors for contracting MDR bacteria during hospitalization in a tertiary pediatric department. The incidence of symptomatic MDR Infection among those colonized should be under close surveillance and long-term screening for those children is required. An institutional screening program for MDR especially in PICU might be discussed in regards to cost effectiveness.